Numerical analysis of the crack inspections using hybrid approach for the application the circular cantilever rods - Raheemah, Saddam Hussein; Fadheel, Kareem Idan; Hassan, Qais Hussein; Mohammed Aned, Ashham; Turki Al-Taie, Alaa Abdulazeez; Kadhim Sharaf, Hussein (Universiti Putra Malaysia Press, 2021)
The present study aims to investigate crack presence in a rigid steel beam so that it can be considered in structural design. A finite element method (FEM) had been used with the Ansys 16.1 software to simulate the whole steel body with three different forces and moments with a magnitude force subjected at the free end of the beam. The steel rod had been considered as simple cantilever to be modelled by the software. Von Mises stress had been considered in the simulation process where the maximum value of stress due to applied load and moment was 1.9 MPa. Total deformation of the whole body had also been considered to instigate the maximum deformation (4.3mm) due to applied loads and moments. Furthermore, MATLAB and through fuzzy logic had been used to assist in the investigation of cracks. Both approaches had been governed by the EulerBernoulli theory for free vibration of motion equations. The other aim of this study is to evaluate results received from the Ansys with MATLAB for the same boundary conditions as the case.